METHODS FOR DETECTING CREATIVE ACCOUNTING PRACTICES AND THEIR IMPACT ON INVESTMENT DECISIONS UNDER INTERNATIONAL FINANCIAL REPORTING STANDARDS (AN APPLIED STUDY IN A SAMPLE OF BANKS LISTED ON THE IRAQI STOCK EXCHANGE ( - Zina Adnan Kareem (Scholar Express Journals, 2023)
The research aims to address the Jones model as one of the appropriate models for detecting creative accounting methods and explaining their causes, as well as finding methods that help in searching for any warning signs indicating the presence of manipulation in financial information, as well as explaining the importance of this in helping to rationalize investment decisions. The research was applied in the research sample to a group of Iraqi banks listed on the Iraqi Stock Exchange for the period from 2013 to 2018. The research reached a set of conclusions, the most important of which was that creative accounting is one of the aspects of manipulating financial statement data for the purpose of misleading by exploiting flexibility in applying accounting and professional standards, principles, policies and procedures, as well as the presence of many models and indicators that regulatory authorities can adopt in revealing accounting practices. Creativity. Or which gives a warning that there is a possibility that these practices will be used to manipulate the financial statements for the purpose of helping to rationalize investment decisions in accordance with different environmental requirements.
Keywords: requirements; regulatory; research